2022
DOI: 10.3390/vetsci9040185
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Performances and Effects on Lipid and Cytokine Production of a Ceruminolytic Ear Cleaner in Canine Erythemato-Ceruminous Otitis Externa

Abstract: Erythemato-ceruminous otitis externa (ECOE) is the most common type of otitis in dogs and is generally associated with bacterial and/or yeast infections. The performance of an ear cleaner was assessed over two weeks in canine ECOE, associated with a mild or moderate secondary infection, in a prospective open-label study. Forty ear canals with ECOE that did not receive any type of aural treatment and were not cleaned for 7 days were included. Pruritus (PS), 0–3 Otitis Index Score (OTIS-3) and 0–4 scale cytology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Similar findings have been reported with IL-8 concentrations in the ear canal of ceruminous in dogs with OE were significantly decreased with the reduction of Malassezia organisms due to the use of ear cleaners (12). Previous studies have shown that Malassezia species induce IL-8 secretion by human keratinocytes (9,(14)(15)(16). Therefore, the increased IL-8/CXCL8 concentrations in ceruminous Malassezia OE may be related to the high number of Malassezia organisms that induce IL-8/CXCL8 secretion from epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Similar findings have been reported with IL-8 concentrations in the ear canal of ceruminous in dogs with OE were significantly decreased with the reduction of Malassezia organisms due to the use of ear cleaners (12). Previous studies have shown that Malassezia species induce IL-8 secretion by human keratinocytes (9,(14)(15)(16). Therefore, the increased IL-8/CXCL8 concentrations in ceruminous Malassezia OE may be related to the high number of Malassezia organisms that induce IL-8/CXCL8 secretion from epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Ear cleaning is therefore essential in managing otitis 14,40 . In one study of a ceruminolytic/ceruminosolvent ear cleaner in erythroceruminous otitis, cleaning resulted in improved clinical and cytological scores, decreased debris, and altered lipid profiles 41 . The latter effect may promote a more diverse microbiome as a topical 'prebiotic'.…”
Section: Epidermal Migration and Ear Cleaningmentioning
confidence: 99%
“…Antimicrobial, antimycotic, and anti-inflammatory medications are used as pharmacological support, but treatment failure and antimicrobial resistance are coercing the development of alternative approaches based on phytotherapeutic agents [28]. The most common bacteria isolated in canine OE cultures are Staphylococcus pseudintermedius, P. aeruginosa, S. aureus, Enterococcus spp., Corynebacterium spp., Streptococcus spp., and Escherichia coli [27][28][29][30][31]. Colonization by opportunistic bacteria, yeast (such as Malassezia), and antimicrobial resistance could complicate the pathology and can pose a therapeutic challenge for veterinarians.…”
Section: Introductionmentioning
confidence: 99%